2009
DOI: 10.1007/s10201-009-0262-z
|View full text |Cite
|
Sign up to set email alerts
|

Variability of nutrients and phytoplankton biomass in a shallow brackish water ecosystem (Chilika Lagoon, India)

Abstract: Seasonal and spatial variations in water quality parameters, such as nutrients [NH 4 ? -N, NO 2 --N, NO 3 --N, PO 4 3--P, total nitrogen (TN) and total phosphorus (TP)], Secchi disc depth, salinity, dissolved oxygen, chlorophyll a, primary productivity and phytoplankton standing stock, were studied in Chilika Lagoon (from 27 sampling locations) during 2001-2003 to assess the present ecological status. The study was undertaken after a major hydrological intervention in September 2000, which connected the lago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 26 publications
6
51
0
Order By: Relevance
“…The Chilika wetland ecosystem is one of such wetland where unique assemblage of marine, brackish water and fresh water ecosystem is seen. It is located on the east coast of India and regarded as the largest tropical brackish water lagoon in Asia (Panigrahi 2009;CDA 2008). This lagoon is enriched with high fisheries resource that supports the livelihood of fisher folk, for a population more than 2 lakhs (CDA 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Chilika wetland ecosystem is one of such wetland where unique assemblage of marine, brackish water and fresh water ecosystem is seen. It is located on the east coast of India and regarded as the largest tropical brackish water lagoon in Asia (Panigrahi 2009;CDA 2008). This lagoon is enriched with high fisheries resource that supports the livelihood of fisher folk, for a population more than 2 lakhs (CDA 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Naming a few Bhattacharya et al, 1994;Panigrahy (2000); Chandramohan and Nayak,(1994) have enumerated the geology, geomorphology and tidal variation in the lagoon. Panda et al, (2006) have studied the distribution of trace metals in the surficial sediment, while Sahu and Adhikary, (1999) and Shaw et al, (2000) elucidated the distribution of seaweed and macrophytes, Panigrahy(1985); Panigrahi (2006Panigrahi ( ,2007Panigrahi ( ,2009) have described for phytoplankton and primary productivity potentiality of the lagoon where as Nayak et al, (2004) ;Panigrahi, (2009) and Mohapatra et al, (2007) studied the water chemistry and fishery production of the lake and the works of Zoological Survey of India regarding fauna of Chilika lake (ZSI 1995). Perusal of the literature has suggested that attention towards the study of macrobenthic organisms in the Chilika lake is still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we did not encounter any live specimens beyond 4 cm, with the majority of the density restricted to the surface 0−2 cm fractions in most of the samples. The studied environment of Chilika lagoon has previously been reported to be under seasonal influence due to the southwestern monsoon-induced precipitation and freshwater influx from the Ma hanadi basin (Panigrahi et al 2009, Srichandran et al 2015a. During the study period, the maximum precipitation was observed during the months of July−October, which corresponds to the monsoon season in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient dynamics observed in this shallow (< 2 m) water body are influenced by monsoonal precipitation (Nayak & Behera 2004, Panigrahi et al 2009), along with physiological factors and carbon dynamics (Muduli et al 2012(Muduli et al , 2013. Previous studies of the lagoon have identified seasonal variations within the phytoplankton (Panigrahi et al 2009, Srichandan et al 2015a) and zooplankton (Naik et al 2008) communities of the water column; however, studies investigating seasonal patterning within the benthic bottom-dwelling communities are not available. Previous reports on the diversity of benthic foraminifers from this lagoon have reported extremely low values (Jayalakshmy & Rao 2001, Kumar et al 2015.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation